REIMAGINING NUMERACY LEARNING IN INDONESIAN PRIMARY SCHOOLS: DESIGNING ASSESSMENTS AND RETHINKING POLICY IN LAMONGAN REGENCY - HUMAIRAH, ORIZA ZATIVALEN, SYAIPUTRA WAHYUDA MUSA DININGRAT, RIZKA NOVI IRMANINGRUM, ARI SUSANDI, RIZKY AMELIA (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Measurement of numeracy skills is given in solving problems in various types of appropriate contexts. The assessment created is still in the development stage so that trials are needed to examine theoretical perspectives regarding the design of numeracy AKM questions. The numeracy ability assessment developed aims to measure students' thinking abilities in using concepts, procedures, facts, mathematical tools to solve everyday problems that are relevant in various contexts. Some of the things tested in the numeracy ability assessment are numbers, geometry and measurement, data and uncertainty, and algebra. This study uses a qualitative approach with a qualitative research type. The research procedure can produce descriptive data in the form of spoken or written words from humans and observable behavior or actions .The subjects of this study were 36 teachers and 200 elementary school students in Lamongan Regency, East Java Province, from six different sub-districts: Babat, Karanggeneng, Brondong, Tikung, Sukodadi, and Made. Lamongan Regency was chosen as the research location because its socio-cultural, educational, and numeracy landscape still requires a specialized approach, and the absence of a transformative policy for mathematics learning, resulting in many schools still experiencing low numeracy skills